Glaucoma: from pathogenic mechanisms to retinal glial cell response to damage - Fernández-Albarral, Jose A.; Ramírez, Ana I.; de Hoz, Rosa; Matamoros, José A.; Salobrar-García, Elena; Elvira-Hurtado, Lorena; López-Cuenca, Inés; Sánchez-Puebla, Lidia; Salazar, Juan J.; Ramírez, José M. (Frontiers in Cellular Neuroscience, 2024)
Glaucoma is a neurodegenerative disease of the retina characterized by the irreversible loss of retinal ganglion cells (RGCs) leading to visual loss. Degeneration of RGCs and loss of their axons, as well as damage and remodeling of the lamina cribrosa are the main events in the pathogenesis of glaucoma. Different molecular pathways are involved in RGC death, which are triggered and exacerbated as a consequence of a number of risk factors such as elevated intraocular pressure (IOP), age, ocular biomechanics, or low ocular perfusion pressure. Increased IOP is one of the most important risk factors associated with this pathology and the only one for which treatment is currently available, nevertheless, on many cases the progression of the disease continues, despite IOP control. Thus, the IOP elevation is not the only trigger of glaucomatous damage, showing the evidence that other factors can induce RGCs death in this pathology, would be involved in the advance of glaucomatous neurodegeneration. The underlying mechanisms driving the neurodegenerative process in glaucoma include ischemia/hypoxia, mitochondrial dysfunction, oxidative stress and neuroinflammation. In glaucoma, like as other neurodegenerative disorders, the immune system is involved and immunoregulation is conducted mainly by glial cells, microglia, astrocytes, and Müller cells. The increase in IOP produces the activation of glial cells in the retinal tissue. Chronic activation of glial cells in glaucoma may provoke a proinflammatory state at the retinal level inducing blood retinal barrier disruption and RGCs death. The modulation of the immune response in glaucoma as well as the activation of glial cells constitute an interesting new approach in the treatment of glaucoma.